Pengembangan Laboratorium Virtual Analisis Kalsium Metode Kompleksometri sebagai Media Pembelajaran Daring Analisis Zat Gizi Mikro - Risti Rosmiati; Dina Ampera; Hardi Firmansyah (Jurnal Ilmiah Wahana Pendidikan, 2020)
The Covid-19 pandemic has led to the online learning system, so it is necessary to develop an alternative learning media to support it. The study objective was to develop a virtual laboratory of complexometric method calcium analysis as an online learning media for micronutrient analysis courses. Research and development studies were carried out in June-August 2020 using the Four-D model (Define, Design, Develop, Disseminate). The defined stage analysis results indicated the need for alternative learning media integrated with technologies such as virtual laboratories. The virtual laboratory of complexometric method calcium analysis contains a title and learning outcome, a review of the analysis principles presented in the dialogue simulation, an explanation of the analysis steps, the analysis process using a 3D simulation, a discussion of calculation methods, and an interactive quiz to evaluate the student comprehension. Expert validation showed that it was feasible as a learning media and had a good student perception. Therefore, it was feasible as an online learning media for the micronutrient analysis course.